2021
DOI: 10.1016/j.dam.2021.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Dominating sets reconfiguration under token sliding

Abstract: Let G be a graph and Ds and Dt be two dominating sets of G of size k. Does there exist a sequence D0 = Ds, D1, . . . , D −1 , D = Dt of dominating sets of G such that Di+1 can be obtained from Di by replacing one vertex with one of its neighbors? In this paper, we investigate the complexity of this decision problem. We first prove that this problem is PSPACE-complete, even when restricted to split, bipartite or bounded treewidth graphs. On the other hand, we prove that it can be solved in polynomial time on du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Finally, we consider what happens when we consider ℓ to be a parameter instead. Consider Timed Independent Set Reconfiguration (or equivalently Binary Timed Independent Set Reconfiguration) is parameterized by the size of the independent set and the length of the sequence 3 . Mouawad et al [17] showed that this problem is W [1]-hard 4 .…”
Section: Independent Set Reconfigurationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we consider what happens when we consider ℓ to be a parameter instead. Consider Timed Independent Set Reconfiguration (or equivalently Binary Timed Independent Set Reconfiguration) is parameterized by the size of the independent set and the length of the sequence 3 . Mouawad et al [17] showed that this problem is W [1]-hard 4 .…”
Section: Independent Set Reconfigurationmentioning
confidence: 99%
“…The dominating set reconfiguration problem is similar to the independent set reconfiguration problem, but in this case all sets in the sequence must form a dominating set in the graph. This again gives a PSPACE-complete problem [10], even for simple graph classes such as planar graphs and classes of bounded bandwidth [7], see also [3]. We define the parameterized problems Dominating Set Reconfiguration, Timed Dominating Set Reconfiguration and Binary Timed Dominating Set Reconfiguration similarly as their independent set counterparts, again parameterized by the number of tokens.…”
Section: Dominating Set Reconfigurationmentioning
confidence: 99%
“…The rearrangement of atoms can be framed as a reconfiguration problem; the reconfiguration framework [2,3,5,[12][13][14][15]18] characterizes the transformation between configurations by means of a sequence of reconfiguration steps. By representing atoms as tokens, we can define each configuration of unlabelled tokens as a subset of vertices of a graph, indicating that there is a token placed on each vertex in the subset; for tokens with labels, a labelled configuration can be represented as a mapping of distinct labels to a subset of the vertices.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, they gave linear-time algorithms for trees, interval graphs, and cographs. Bonamy et al [8] showed that DSR-TS is PSPACE-complete on split, bipartite and bounded treewidth graphs and polynomial-time solvable on dually chordal graphs and cographs. Bousquet and Joffard [13] showed that the problem is polynomial-time solvable on circulararc graphs and PSPACE-complete on circle graphs.…”
Section: Introductionmentioning
confidence: 99%